Seeking freedom : the untold story of Fortress Monroe and the ending of slavery in America - Castrovilla, Selene, 1966- (Calkins Creek, 2022)
A young African American slave boy named George Scott sneaks into the Fortress Monroe after he sees other slaves enter and not be cast out. Making friends there with the commander, Union Major General Benjamin Butler, George Scott and Butler work together to save the fortress from the Confederate soldiers seeking to take it down and recapture the escaped slaves inside.